2007
DOI: 10.1128/ec.00318-07
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptional Profiling of the Cyclic AMP-Dependent Signaling Pathway during Morphogenic Transitions of Candida albicans

Abstract: Candida albicans is an opportunistic human fungal pathogen that causes systemic candidiasis as well as superficial mucosal candidiasis. In response to the host environment, C. albicans transitions between yeast and hyphal forms. In particular, hyphal growth is important in facilitating adhesion and invasion of host tissues, concomitant with the expression of various hypha-specific virulence factors. In previous work, we showed that the cyclic AMP (cAMP) signaling pathway plays a crucial role in morphogenic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 92 publications
1
52
2
1
Order By: Relevance
“…To test this hypothesis, we measured the level of expression of CAT1 in response to 10 mM H 2 O 2 in WT and ras1/ras1 cells. Consistent with previous data (1,24), the level of CAT1 transcripts was higher in the ras1/ras1 than in the WT cells (Fig. 5B).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…To test this hypothesis, we measured the level of expression of CAT1 in response to 10 mM H 2 O 2 in WT and ras1/ras1 cells. Consistent with previous data (1,24), the level of CAT1 transcripts was higher in the ras1/ras1 than in the WT cells (Fig. 5B).…”
Section: Resultssupporting
confidence: 92%
“…We have previously reported that farnesol inhibits Ras1-adenylate cyclase signaling, leading to the inhibition of hyphal growth (10). As the Ras-cAMP cascade represses the expression of OX stress response genes (1,24,66), we sought to test the hypothesis that farnesol-mediated inhibition of this pathway leads to the increased transcription of CAT1 and protection against ROS in yeast. To do this, we measured the effects of farnesol on ras1/ras1 and cyr1/cyr1 mutant survival after treatment with H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…cAMP levels are also negatively regulated by a high-affinity phosphodiesterase, Pde2 (orf19.2972), and a low-affinity phosphodiesterase, Pde1 (orf19.4235), that increase the rate of cAMP break- down. Increased PDE2 expression in hyphae counteracts the Srv2-dependent synthesis of cAMP and limits filament formation (41), while loss-of-function mutations in PDE2 increase cAMP levels and lead to constitutive activation of the pathway and increased filament formation (42)(43)(44). Pde1 mediates repression of cAMP signaling in response to glucose and intracellular acidification (45).…”
Section: Ras/camp/pka Signaling In C Albicansmentioning
confidence: 99%